ChemInform Abstract: A Bidentate Ligand Immobilized on Silica via a Tripodal Linker Unit: Preparation and Application to Suzuki—Miyaura Coupling. Issue 33 (25th July 2013) - Onozawa, Shun‐ya; Miyaji, Takayuki; Fukaya, Norihisa; Yoshinaga, Michiyo; Ueda, Masae; Takagi, Yukio; Yasuda, Hiroyuki
Abstract A Pd‐complex catalyst prepared from 1, 3‐bis(diphenylphosphino)propane‐functionalized silica support shows moderate activity for the Suzuki—Miyaura coupling reaction of aryl chloride with phenylboronic acid.